PATTERNS OF SOCIAL RELATIONS BETWEEN ETHNICS TO MAKE SOCIAL INTEGRATION OF HISTORICAL EDUCATION STUDENTS OF THE PGRI IKIP OF PONTIANAK: POLA RELASI SOSIAL ANTAR ETNIK UNTUK MEWUJUDKNAN INTEGRASI SOSIAL MAHASISWA PENDIDIKAN SEJARAH IKIP PGRI PONTIANAK - Saiful Bahri; Emi Tipuk Lestari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
The purpose of this research is to analyze the pattern of social relations between Madura, Dayak, China and Malay that can realize the values of social integration in IKIP PGRI Pontianak. This research was carried out using qualitative approach with phenomenological form or method, descriptive analysis and qualitative approach. The research subjects were Dayak, Madura, Malayu and Chinese ethnicities as well as non-ethnic colors from Dayak, Madura, Malay and Chinese. The location of this research is at the campus of IKIP PGRI Pontianak which is multiethnic for its students. Data collection techniques used in this research are observations, interviews, and documentation. Instruments or data collection tools include observation sheets, interview guidelines and docemntasi. Data management of the research results was carried out with interactive model analysis techniques from Miles and Huberman which include components: 1) Data collection, 2) data reduction, 3) data feed and 4) conclusion drawing (verification). Analysis is carried out continuously from the beginning of data collection until the verification process that takes place from the beginning of the research until the research is completed. The results of the study are 1) The fact of social relations between ethnic Dayak, Madura, Malay and China gave birth to solidarity between solidaritai groups can be in group (in the ethnic itself) or outside the ethnic group itself. The inter-ethnic mixing of Dayak, Madura, Malay and Chinese when they were in the lecture activities led to the loss of identity. Identity will be when they're not in college. 2) The integration found in dayak, Chinese, Malay and Madura ethnic culture wisdom is categorized into normative integration. Normative integration is a social bond that occurs because of a consensus on basic values and norms.3)The pattern of social relations between Dayak, China, Malay and Madura that is described above shows that an associative or positive pattern has been formed. The advice is 1. Other researchers: Limitations of the results of this study can be a study material for other researchers in West Kalimantan and in the territory of the Republic of Indonesia